Strategi Guru Pendidikan Agama Islam dalam Membentuk Karakter Siswa Muslim Melalui Program Khusus di SMP Negeri 1 Gatak - Ellynia Eva Kusuma Dewi; Mohammad Zakki Azani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to investigate the strategies of Islamic Religious Education teachers in shaping the character of Muslim students through special programs at SMP Negeri 1 Gatak, as well as the supporting and inhibiting factors in their implementation. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and literature studies. The results of character building of Muslim students is carried out through special programs such as minor ceremonies, scouting, Qur’anic Reading and Writing, second week Friday morning recitations, morning prayers,and the mandatory ownership of a daily prayer logbook for every Muslim student. The strategies applied by the Islamic Religious Education teachers include exemplification (role modeling), habituation, counselling, and active student involvement in every activity. These programs are supported by the cooperation among the school, teachers, and parents, although there are obstacles such as fluctuating student motivation, schedule conflicts with extracurricular activities, and communication barriers. Overall, the implemented special programs have a positive impact on the character building of Muslim students, particularly in enhancing their religious attitudes, discipline, responsibility, and good behavior.